PSYCHO-SOCIAL FACTORS AS PREDICTORS OF SCHOOL ADJUSTMENT AMONG SECONDARY SCHOOL STUDENTS WITH VISUAL IMPAIRMENT IN SOUTHEASTERN NIGERIA (2024)
School adjustment is a veritable means of enhancing school engagement and academic achievement. However, Students with Visual Impairment (SwVI) in secondary schools find it difficult to cope with the demands of the school environment with complexities, such as multiple classrooms, un-adapted curriculum and lack of appropriate assistive technologies. As a result, many SwVI have to contend with poor academic achievement due to poor school adjustment. Previous studies have focused more on teaching strategies for improving academic performance and social adjustment with little attention paid to the influence of psycho-social factors on school adjustment among SwVI. This study, therefore, was designed to examine how self-concept, emotional intelligence, peer relationship, teacher-student relationship, self-efficacy and gender are implicated in the school adjustment of SwVI in southeastern Nigeria. The Lev Vygotsky’s Social Development and Bandura’s Social Learning theories provided the framework, while the survey design of correlational type was adopted. The 13 special junior and senior secondary schools (public and private), with educational facilities for SwVI in the five states of Southeastern Nigeria (Abia-3), (Anambra-5), (Ebonyi-1), (Enugu-3) and Imo (1) were enumerated. A screening conducted using the Snellen Chart revealed that there were 120 SwVI in the special secondary schools. Ninety six SwVI who consented to participating in the study were purposively selected. The instruments used were School Adjustment (r=0.82), Self-concept (r=0.80), Emotional Intelligence (r=0.80), Peer Relationship (r=0.79), Teacher-student Relationship (r=0.81) and Self-efficacy (rN=0.85) scales. Data were analysed using descriptive statistics, Pearson’s product moment correlation, multiple regression and t-test at 0.05 level of significance. The respondents’ age was 17.00±3.20 years, 61.5% were male, while 58.4% were in junior secondary school. The SwVI were from middle socio-economic families (65.6%), those with moderate visual impairments (51.0%) and those with acquired onset impairment (63.5%). The SwVI level of school adjustment was high 2.65 against a norm of 2.50. Peer relationship (r = 0.58), teacher-student relationship (r = 0.55) self-concept (r = 0.49), self-efficacy (r = 0.44) positively correlated with school adjustment but emotional intelligence did not. The predictor variables had a joint prediction on school adjustment (F(5,90) = 14.39; Adj. R2 = 14.0); accounting for 14.0% of its variance. The peer relationship (β = 0.27), teacher-student relationship (β = 0.25), self-concept (β = 0.23), emotional intelligence (β = 0.16) and self-efficacy (β = 0.13) had relative contributions to school adjustment, while emotional intelligence and self-efficacy did not. There was no gender difference in the school adjustment of male and female SwVI. Peer relationship, teacher-student relationship, self-concept and self-efficacy influenced school adjustment of students with visual impairment in secondary schools in Southeastern Nigeria. Therefore, teachers and parents should pay close attention to these factors to ensure effective school adjustment among students with visual impairment.